Carbon material, method for preparing the same, and use thereof

CN123017965APending Publication Date: 2026-10-30LANXI ZHIDE ADVANCED MATERIALS CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510475718.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-04-16
Publication Date
2026-10-30

AI Technical Summary

Technical Problem

[0006]本发明的目的之一在于提供一种碳材料,具有丰富的2~10nm介孔,且在介孔内壁设置氧化物层,解决了传统碳材料的结构强度低的问题

Benefits of technology

[0047]本发明提供了一种碳材料,多孔碳骨架的孔壁存在氧化物界面层,使其在作为复合材料载体时起到双重增强机制:氧化物层本身的增强作用,以及碳与负载物之间的结合力因氧化物界面而增强,因此提高了复合材料的结构强度;作为催化剂时,氧化物薄膜或氧化物岛的存在可以提供缺陷位点或活性位点,提高催化活性,使得碳材料可以拓展其在选择性特异性吸附、高强度复合材料等方面的应用。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN123017965A_ABST
    Figure CN123017965A_ABST
Patent Text Reader

Abstract

The application discloses a carbon material and a preparation method and application thereof, and relates to the technical field of batteries. The carbon material is uniformly loaded with oxides on the inner wall of pores, the oxides in the carbon material are coated on the pore wall of the carbon material in the form of an oxide film, and / or the oxides exist in the form of oxide islands on the pore wall of the carbon material. The pore wall of the porous carbon skeleton has an oxide interface layer, which plays a double enhancement mechanism when serving as a composite carrier: the enhancement effect of the oxide layer itself, and the bonding force between the carbon and the load is enhanced due to the oxide interface, thereby improving the structural strength of the composite; when serving as a catalyst, the existence of the oxide film or the oxide island can provide defect sites or active sites, improve the catalytic activity, and make the carbon material capable of expanding the application thereof in selective specific adsorption, high-strength composite materials and the like. The silicon-carbon composite material using the carbon material as a substrate has high structural strength and cycle stability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of battery technology, and in particular to a carbon material, its preparation method, and its application. Background Technology

[0002] Porous carbon materials possess advantages such as large specific surface area, well-developed pore structure, and good chemical stability, demonstrating broad application prospects in multiple research fields. Their preparation methods mainly include activation methods, template methods, and sol-gel methods.

[0003] Due to the wide availability of carbon precursors and the uncontrollable nature of their high-temperature decomposition and pyrolysis, the porous carbon structures in existing technologies exhibit a multi-scale and continuous distribution, consisting of micropores, mesopores, and macropores. The pore distribution of carbon materials has a significant impact on their application performance, especially in adsorption, catalysis, and supported applications.

[0004] Silicon-carbon composite materials combine the high capacity of silicon with the high conductivity of carbon, making them highly favored by the lithium-ion battery industry in recent years, with CVD silicon-carbon anodes being the leading example. CVD silicon-carbon anodes utilize porous carbon as a framework, with silicon deposited within the porous carbon channels. The pore size of the porous carbon determines the upper limit of the silicon particle size. Currently, the commonly used porous carbon is microporous carbon, which is prone to pore blockage during silicon deposition, resulting in a large number of closed pores within the composite material. This reduces the material's structural strength and makes it difficult to withstand pressure during electrode fabrication, leading to a significant decrease in the initial coulombic efficiency after compaction. Furthermore, since composite materials require a certain silicon content to achieve high capacity, this necessitates a sufficiently large pore volume in the porous carbon. However, with traditional porous carbon, a large pore volume results in correspondingly thin pore walls, also reducing the structural strength of the composite material and deteriorating subsequent processing and cycle performance.

[0005] In view of this, the present invention is hereby proposed. Summary of the Invention

[0006] One of the objectives of this invention is to provide a carbon material with abundant 2-10 nm mesopores, and an oxide layer is provided on the inner wall of the mesopores, thereby solving the problem of low structural strength of traditional carbon materials.

[0007] The second objective of this invention is to provide a method for preparing carbon materials, thereby solving the problem of low structural strength of carbon materials in the prior art.

[0008] The third objective of this invention is to provide a silicon-carbon composite material in which silicon nanoparticles are controlled at 2-5 nm, and an oxide interface layer exists between the porous carbon pore walls and the silicon nanoparticles, thus solving the problems of low structural strength, low initial efficiency under high pressure density, and poor cycle life of existing silicon-carbon composite materials in lithium-ion battery applications.

[0009] The fourth objective of this invention is to provide a negative electrode that improves the structural stability of silicon-carbon negative electrode materials, enhances the initial coulombic efficiency, and improves cycle life and rate performance.

[0010] A fifth objective of this invention is to provide a battery that utilizes the negative electrode to optimize overall battery performance, thereby improving energy density, cycle stability, and lifespan. To achieve the above objectives of this invention, the following technical solution is adopted:

[0011] In a first aspect, the present invention provides a carbon material comprising a porous carbon framework and an oxide, wherein the oxide is located on the inner wall of the pores of the porous carbon framework, and the oxide is coated on the pore walls of the carbon material in the form of an oxide film; and / or, the oxide exists on the pore walls of the carbon material in the form of oxide islands.

[0012] Furthermore, the oxide has a mass content of 0.2% to 5.0%; the carbon material contains mesopores with a pore size of 2 to 10 nm.

[0013] Furthermore, the oxide in the carbon material is one or more of silicon oxide, aluminum oxide, titanium oxide, aluminum silicate oxide, or magnesium oxide; preferably, the hard template agent is a porous material; more preferably, the hard template agent is an ordered mesoporous material.

[0014] Furthermore, the mass content of oxides in the carbon material is 0.2% to 1.0%;

[0015] And / or, the specific surface area of ​​the carbon material is 200–2000 m². 2 / g, preferably, the specific surface area of ​​the carbon material is 500-1300 m² / g. 2 / g;

[0016] And / or, the pore volume of the carbon material is 0.2–1.5 cm³. 3 / g;

[0017] And / or, the average pore size of the carbon material is 2 to 10 nm;

[0018] And / or, the carbon material has a mesoporous content of 75% to 100%;

[0019] And / or, the pore volume of the 2-10 nm mesopores in the carbon material accounts for 75%-100% of the pore volume;

[0020] And / or, the pore size of the intermediate pores in the carbon material is 2-5 nm;

[0021] And / or, the carbon material is an ordered mesoporous material.

[0022] Secondly, the present invention provides a method for preparing a carbon material, wherein the method comprises mixing a hard template agent with a carbon precursor, carbonizing the mixture, removing the hard template agent, and obtaining the carbon material; the carbon material is a mesoporous carbon material; the carbon precursor is an organic compound containing a carbon source, wherein the carbon source is one or more of polysaccharides, resins, or asphalt.

[0023] Furthermore, the hard template agent includes one or more of silicon oxide, aluminum oxide, titanium oxide, aluminum silicate, or magnesium oxide; the hard template agent is a porous material.

[0024] And / or, the mass ratio of the carbon precursor to the hard template agent is 1:50 to 10:1;

[0025] And / or, the mixing includes solid-phase mixing or liquid-phase mixing, wherein the solid-phase mixing is to grind or ball-mill the carbon precursor and the hard template agent; and the liquid-phase mixing is to disperse the carbon precursor and the hard template agent in a solvent, wherein the solvent is pure water and / or ethanol, and the solvent is removed by solvent evaporation and / or solid-liquid separation.

[0026] And / or, the carbonization temperature is 500–1000°C;

[0027] And / or, the method of removing the hard template agent is to treat it with one or more of HF, NaOH, KOH, Na2CO3, K2CO3, HCl, HNO3 or H2SO4 at 0 to 110°C, and then clean and dry it;

[0028] And / or, the method for preparing the carbon material further includes one or more of water activation, alkali activation, or defunctionalization treatment.

[0029] Furthermore, the preparation method of the hard template agent is as follows: the pH of a mixed slurry containing a surfactant, a catalyst and a hard template precursor is adjusted, and after hydrothermal treatment, the slurry is filtered, dried and calcined to obtain the hard template agent.

[0030] Furthermore, the mass ratio of the surfactant to the hard template precursor is 1:100 to 100:1, preferably 1:10 to 10:1;

[0031] Furthermore, the mass ratio of the surfactant to the catalyst is 1:30 to 30:1, preferably 1:10 to 10:1;

[0032] Furthermore, the method for preparing the mixed slurry containing surfactant, catalyst and hard template precursor is to mix solution A containing surfactant and catalyst with solution B containing hard template precursor and adjust the pH.

[0033] Furthermore, the surfactant is one or more of cationic surfactants, anionic surfactants, amphoteric surfactants, and nonionic surfactants;

[0034] Furthermore, the catalyst includes an acid solution or an alkaline solution;

[0035] Furthermore, the hard template precursor includes one or more of the following: tetraethyl orthosilicate, silane, silica sol, silicon tetrachloride, sodium silicate, potassium silicate, aluminum nitrate nonahydrate, aluminum isopropoxide, or aluminum sec-butoxide.

[0036] Furthermore, the pH of the mixed slurry is one of acidic, neutral, or alkaline, wherein the acidic pH is 1-5, the neutral pH is 6.5-7.5, and the alkaline pH is 9-13.

[0037] Furthermore, the mixed slurry is subjected to hydrothermal treatment under the pH conditions, and the hydrothermal temperature is 0–220°C;

[0038] Furthermore, the calcination temperature is 200–800°C, preferably 400–600°C.

[0039] Thirdly, the present invention provides a silicon-carbon composite material comprising carbon material and silicon nanoparticles, wherein the size of the silicon nanoparticles is 2-5 nm; an oxide interface exists between the carbon material and the silicon nanoparticles, wherein the mass content of the oxide is 0.04%-4.0%.

[0040] Furthermore, the carbon material is the carbon material provided in the first aspect of the present invention, or the carbon material prepared by the method for preparing carbon material provided in the second aspect of the present invention.

[0041] Furthermore, the silicon-carbon composite material is obtained by chemical vapor deposition of a silicon-containing precursor on the carbon material at 150–1000°C; preferably, the silicon-containing precursor is selected from one or more of silane, ethyl silane, propane, halosilane, polysilane, thiophene and its derivatives or silanium and its derivatives.

[0042] Furthermore, a heteroatom-containing precursor is introduced during the chemical vapor deposition process; the heteroatom-containing precursor includes at least one of an oxygen-containing precursor, a carbon-containing precursor, a nitrogen-containing precursor, a phosphorus-containing precursor, a sulfur-containing precursor, or a boron-containing precursor; preferably, the silicon-containing precursor and the heteroatom-containing precursor are contacted with the porous substrate in the following ways: the silicon-containing precursor and the heteroatom-containing precursor are alternately contacted with the porous substrate; or, the silicon-containing precursor and the heteroatom-containing precursor are simultaneously contacted with the porous substrate; or, the silicon-containing precursor and a mixed gas containing the silicon-containing precursor and the heteroatom-containing precursor are alternately contacted with the porous substrate; preferably, the silicon-containing precursor is continuously contacted with the porous substrate, and the heteroatom-containing precursor is intermittently introduced during this process.

[0043] Furthermore, the silicon-carbon composite material includes a coating layer located on the surface of the silicon-carbon composite material; preferably, the material of the coating layer is selected from at least one of solid electrolytes, conductive polymers, carbonaceous materials, metals, alloys, metal oxides, metal hydroxides, halogen-containing compounds, nitrogen-containing compounds, phosphorus-containing compounds, boron-containing compounds, and sulfur-containing compounds; more preferably, the material of the coating layer is a carbonaceous material.

[0044] Fourthly, the present invention provides a negative electrode comprising a negative electrode active material, wherein the negative electrode active material comprises the silicon-carbon composite material provided in the third aspect of the present invention.

[0045] Fifthly, the present invention provides a battery comprising a positive electrode, a negative electrode, a separator or an electrolyte, wherein the negative electrode comprises a negative electrode active material, and the negative electrode active material comprises the silicon-carbon composite material provided in the third aspect of the present invention.

[0046] Compared with the prior art, the present invention has at least the following beneficial effects:

[0047] This invention provides a carbon material in which the pore walls of the porous carbon framework have an oxide interface layer, which enables it to play a dual reinforcing mechanism when used as a composite material carrier: the reinforcing effect of the oxide layer itself, and the enhanced binding force between carbon and the load due to the oxide interface, thus improving the structural strength of the composite material; when used as a catalyst, the presence of oxide films or oxide islands can provide defect sites or active sites, improving catalytic activity, thus enabling the carbon material to expand its applications in selective and specific adsorption, high-strength composite materials, etc.

[0048] This invention provides a silicon-carbon composite material in which silicon nanoparticles are controlled to be 2–5 nm in size, and an oxide interface layer exists between the porous carbon pore walls and the silicon nanoparticles. The size of the silicon nanoparticles in the CVD silicon-carbon composite material is determined by the pore size of its porous carbon framework and the deposition process, with the pore size of the porous carbon framework determining the upper limit of the silicon particle size. By controlling the pore size distribution of the porous carbon framework and employing a suitable deposition process, the size of the silicon nanoparticles is controlled to be 2–5 nm, significantly reducing silicon particle expansion during lithium intercalation and improving its cycle stability. Furthermore, the oxide interface layer between the porous carbon pore walls and the silicon nanoparticles establishes a dual reinforcement mechanism in the composite material: the reinforcing effect of the oxide layer itself, and the enhanced bonding force between carbon and silicon due to the oxide interface. This improves the structural strength of the composite material, resulting in higher high-voltage first-stage efficiency and significantly improved cycle stability in lithium-ion battery applications. Attached Figure Description

[0049] To more clearly illustrate the specific embodiments of the present invention or the technical solutions in the prior art, the drawings used in the description of the specific embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are some embodiments of the present invention. For those skilled in the art, other drawings can be obtained from these drawings without creative effort.

[0050] Figure 1 This is a schematic diagram of the mesoporous carbon structure provided in Embodiment 1 of the present invention;

[0051] Figure 2 The adsorption-desorption isotherm curve of mesoporous carbon provided in Example 1 of the present invention;

[0052] Figure 3 The adsorption-desorption isotherm curve of mesoporous carbon provided in Comparative Example 2 of this invention;

[0053] Figure 4 This is a scanning electron microscope image of mesoporous carbon provided in Embodiment 1 of the present invention. Detailed Implementation

[0054] Unless otherwise defined herein, the scientific and technical terms used in conjunction with this invention shall have the meanings commonly understood by one of ordinary skill in the art. The meaning and scope of terms shall be clear; however, in any case of potential ambiguity, the definitions provided herein shall prevail over any dictionary or foreign definitions. In this application, unless otherwise stated, the use of "or" means "and / or". Furthermore, the use of the term "comprising" and other forms is non-limiting.

[0055] Unless otherwise stated, the methods and techniques of the present invention are generally carried out according to conventional methods well known in the art and as described in various general and more specific references, which are cited and discussed throughout this specification.

[0056] In a first typical embodiment of the present invention, a carbon material is provided, the carbon material comprising a porous carbon framework and oxides, the oxides being located on the inner walls of the pores of the porous carbon framework, the oxides being coated on the pore walls of the carbon material in the form of oxide films; and / or, the oxides existing on the pore walls of the carbon material in the form of oxide islands.

[0057] Compared to existing carbon materials, the carbon material provided by this invention has an oxide interface layer on the pore walls of the porous carbon skeleton, which enables it to play a dual reinforcement mechanism when used as a composite material carrier: the reinforcement effect of the oxide layer itself, and the enhanced binding force between carbon and the load due to the oxide interface, thus improving the structural strength of the composite material; when used as a catalyst, the presence of oxide films or oxide islands can provide defect sites or active sites, improving catalytic activity, thus enabling carbon materials to expand their applications in selective and specific adsorption, high-strength composite materials, etc.

[0058] In some embodiments, the oxide has a mass content of 0.2% to 5.0%; the carbon material comprises mesopores with a pore size of 2 to 10 nm.

[0059] With abundant mesopores ranging from 2 to 10 nm, the small size of the mesopores provides feasibility for precise control of carbon materials in adsorption, heterogeneous catalysis, and preparation of supported composite materials.

[0060] In some embodiments, the mass percentage of the oxide layer can be, but is not limited to, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1.0%, 1.2%, 1.6%, 2.0%, 3.0%, 4.0%, or 5.0%, or any value between 0.2% and 5.0%, preferably between 0.2% and 1.0%.

[0061] In some embodiments, the pore size of the mesopore can be, but is not limited to, 2nm, 3nm, 4nm, 5nm, 6nm, 7nm, 8nm, 9nm or 10nm, or any value between 2 and 10nm, preferably 2 to 5nm.

[0062] In some embodiments, the oxide in the carbon material is one or more of silicon oxide, aluminum oxide, titanium oxide, aluminum silicate oxide, or magnesium oxide; the hard template agent is a porous material.

[0063] In some embodiments, the mass content of oxides in the carbon material is 0.2% to 1.0%.

[0064] In some embodiments, the mesopores constitute 75% to 100% of the pores. The percentage of mesopores in the pores can be, but is not limited to, 75%, 78%, 80%, 83%, 85%, 88%, 90%, 93%, 95%, 98%, or 100%, or any ratio between 75% and 100%.

[0065] In some embodiments, the average pore size of the pores is 2–10 nm. In some embodiments, the specific surface area of ​​the carbon material is 200–2000 m². 2 / g. The specific surface area of ​​the carbon material can be, but is not limited to, 200 m². 2 / g、500m 2 / g、800m 2 / g, 1000m 2 / g、1200m 2 / g, 1500m 2 / g、1800m 2 / g or 2000m 2 / g, or 200-2000m 2 Any value between / g, preferably 500 to 1300m 2 / g; In some embodiments, the pore volume of the carbon material is 0.2–1.5 cm³. 3 / g. The pore volume of the carbon material can be, but is not limited to, 0.2 cm³. 3 / g, 0.4cm 3 / g, 0.6cm 3 / g, 0.8cm 3 / g, 1.0cm 3 / g, 1.2cm 3 / g, 1.4cm 3 / g or 1.5cm 3 / g, or 0.2~1.5cm 3 Any value between / g.

[0066] In some embodiments, the pore volume of mesopores of 2–10 nm in the carbon material accounts for 75%–100% of the total pore volume. In some embodiments, the carbon material is an ordered mesoporous material.

[0067] In a second typical embodiment of the present invention, a method for preparing the above-mentioned carbon material is also provided. The method for preparing the carbon material is to mix a hard template agent with a carbon precursor, carbonize the mixture, remove the hard template agent, and obtain the carbon material. The carbon material is a mesoporous carbon material. The carbon precursor is an organic compound containing a carbon source, and the carbon source is one or more of polysaccharides, resins, or asphalt.

[0068] The organic material containing the carbon source combines with the hard template material to form a carbon-hard template agent composite precursor. The hard template agent is then removed by etching and cleaning, yielding mesoporous carbon with a thin oxide film covering the pore walls. Due to the presence of -CH- and -HO bonds in the raw material, the carbon substrate and oxide in the resulting carbon material form a strong bond, making the oxide film less prone to detachment and exhibiting stronger adhesion. This carbon precursor can be completely dispersed or dissolved in the solvent during mixing and gradually solidifies as the solvent slowly evaporates. Furthermore, this carbon precursor possesses excellent template filling properties and uniform replication ability. For example, it can form low-viscosity solutions with resins and asphalt, which melt upon high-temperature heating and can fully penetrate the nanopores of the hard template, achieving uniform filling. In addition, the aforementioned carbon precursor has cost and advantages for industrial production, being a readily available and inexpensive raw material for bulk chemicals, and the process steps are simple and readily available.

[0069] In a mixed slurry containing a hard template agent and a carbon precursor, the carbon precursor fully fills the pores of the hard template agent during mixing. By changing the average pore size and pore distribution of the hard template agent, various desired mesoporous carbons can be prepared. A small amount of oxide exists as a thin film on the pore walls. The oxide on the inner walls of the mesopores provides new active sites and can serve as structural reinforcement, enabling carbon materials to expand their applications in selective and specific adsorption, high-strength composite materials, and other fields. The method is simple and easy to operate, allowing precise control of the pore size and distribution of the mesoporous carbon material, preparing mesoporous carbon with a regular pore structure. Furthermore, it possesses high specific surface area and excellent physicochemical properties, showing broad application prospects in energy storage, catalysis, and adsorption.

[0070] In some embodiments, the mass ratio of the carbon precursor to the hard template agent is 1:50 to 10:1. The mass ratio of the carbon precursor to the hard template agent can be, but is not limited to, 1:50, 1:40, 1:30, 1:20, 1:10, 1:5, 1:3, 1:2, 1:1, 3:1, 5:1, or 10:1, or any value between 1:50 and 10:1, preferably 1:10 to 5:1.

[0071] In some embodiments, the mixing includes solid-phase mixing or liquid-phase mixing. In some embodiments, solid-phase mixing includes grinding or ball milling the carbon precursor and the hard template agent; in some embodiments, liquid-phase mixing includes dispersing the carbon precursor and the hard template agent in a solvent, the solvent including pure water and / or ethanol. In some embodiments, the solvent is removed by solvent evaporation and / or solid-liquid separation.

[0072] In some embodiments, the carbonization temperature is 500–1000°C. The carbonization temperature can be, but is not limited to, 500°C, 550°C, 600°C, 650°C, 700°C, 750°C, 800°C, 850°C, 900°C, 950°C, or 1000°C, or any value between 500 and 1000°C, preferably 500–700°C.

[0073] Hard template agents can be removed using chemical or physical methods, such as acid etching or alkaline washing. In some embodiments, the removal of hard template agents includes treatment with one or more of HF, NaOH, KOH, Na2CO3, K2CO3, HCl, HNO3, or H2SO4 at 0–110°C, followed by cleaning and drying.

[0074] In some embodiments, the carbonization time is 1 to 6 hours. The carbonization time can be, but is not limited to, 1 hour, 2 hours, 3 hours, 4 hours, 5 hours, or 6 hours, or any value between 1 and 6 hours. In some embodiments, the carbonization heating rate is 1 to 10 °C / min. The carbonization heating rate can be, but is not limited to, 1 °C / min, 2 °C / min, 3 °C / min, 4 °C / min, 5 °C / min, 6 °C / min, 7 °C / min, 8 °C / min, 9 °C / min, or 10 °C / min, or any value between 1 and 10 °C / min.

[0075] In some embodiments, the hard template agent comprises one or more of silicon oxide, aluminum oxide, titanium oxide, aluminum silicate, or magnesium oxide. In some embodiments, the hard template agent is a porous material; more preferably, the hard template agent is an ordered mesoporous material.

[0076] In some embodiments, the preparation method of the carbon material further includes one or more of water activation, alkali activation, or defunctionalization treatment.

[0077] In some embodiments, the preparation method of the hard template agent includes adjusting the pH of a mixed slurry containing a surfactant, a catalyst, and a hard template precursor, followed by hydrothermal treatment, filtration, drying, and calcination to obtain the hard template agent. This method can prepare a hard template agent with a certain average pore size and pore distribution.

[0078] In some embodiments, the mass ratio of the surfactant to the hard template precursor is 1:100 to 100:1. The mass ratio of the surfactant to the hard template precursor can be, but is not limited to, 1:100, 1:80, 1:50, 1:30, 1:10, 1:1, 10:1, 30:1, 50:1, 80:1, or 100:1, or any value between 1:100 and 100:1, preferably 1:10 to 10:1.

[0079] In some embodiments, the mass ratio of the surfactant to the catalyst is 30:1 to 1:30, preferably 1:10 to 10:1.

[0080] In some embodiments, the method for preparing the mixed slurry containing a surfactant, a catalyst, and a hard template precursor includes mixing a solution A containing a surfactant and a catalyst and a solution B containing a hard template precursor. In some embodiments, the surfactant is one or more of cationic surfactants, anionic surfactants, amphoteric surfactants, and nonionic surfactants. In some embodiments, the catalyst includes an acidic or alkaline solution, specifically such as ammonia or hydrochloric acid. In some embodiments, the hard template precursor includes one or more of tetraethyl orthosilicate, silane, silica sol, silicon tetrachloride, sodium silicate, potassium silicate, aluminum nitrate nonahydrate, aluminum isopropoxide, or aluminum sec-butoxide. In some embodiments, the pH of the mixed slurry is acidic, neutral, or alkaline, wherein the acidic pH is 1–5, the neutral pH is 6.5–7.5, and the alkaline pH is 9–13. In some embodiments, the mixed slurry is subjected to hydrothermal treatment under the pH conditions, wherein the hydrothermal temperature is 0–220°C; in some embodiments, the calcination temperature is 200–800°C, preferably 400–600°C.

[0081] In a third typical embodiment of the present invention, a silicon-carbon composite material is also provided, comprising carbon material and silicon nanoparticles, wherein the size of the silicon nanoparticles is 2-5 nm; an oxide interface exists between the carbon material and the silicon nanoparticles, wherein the mass content of the oxide is 0.04%-4.0%.

[0082] The aforementioned carbon material is a mesoporous carbon material, which can effectively alleviate silicon expansion during silicon-carbon anode cycling. Furthermore, the addition of a small amount of oxides to the inner walls of the mesoporous carbon enhances the material's internal ion transport capacity. In lithium-ion batteries, the oxides generate Li₂O during the first charge, effectively buffering the volume changes that occur during the charging and discharging of the silicon-carbon anode, thereby improving its electrochemical long-cycle performance. In addition, the oxide interface layer between the porous carbon pore walls and silicon nanoparticles establishes a dual reinforcement mechanism in the composite material: the reinforcement effect of the oxide layer itself, and the enhanced bonding force between carbon and silicon due to the oxide interface. This improves the structural strength of the composite material, resulting in higher first-cycle efficiency and significantly improved cycle stability in lithium-ion battery applications.

[0083] In some embodiments, the carbon material is the carbon material provided in the first typical embodiment of the present invention, or the carbon material prepared by the preparation method of the second typical embodiment of the present invention.

[0084] In some embodiments, the method for preparing the silicon-carbon composite material includes chemical vapor deposition of a silicon-containing precursor on the carbon material at a temperature of 150–1000°C. In some embodiments, the silicon-containing precursor is selected from one or more of silane, disilane, propane, halosilane, polysilane, thiophene and its derivatives, or silanium and its derivatives. In some embodiments, the chemical vapor deposition includes introducing a heteroatom-containing precursor; the heteroatom-containing precursor includes at least one of an oxygen-containing precursor, a carbon-containing precursor, a nitrogen-containing precursor, a phosphorus-containing precursor, a sulfur-containing precursor, or a boron-containing precursor. In some embodiments, the silicon-containing precursor and the heteroatom-containing precursor are alternately contacted with the carbon material; or, the silicon-containing precursor and the heteroatom-containing precursor are simultaneously contacted with the carbon material; or, the silicon-containing precursor and a mixed gas containing the silicon-containing precursor and the heteroatom-containing precursor are alternately contacted with the carbon material; or, the silicon-containing precursor is continuously contacted with the porous matrix, during which the heteroatom-containing precursor is intermittently introduced.

[0085] In some embodiments, the silicon-carbon composite material further includes a coating layer located on the surface of the silicon-carbon composite material. In some embodiments, the material of the coating layer includes at least one selected from solid electrolytes, conductive polymers, carbonaceous materials, metals, alloys, metal oxides, metal hydroxides, halogen-containing compounds, nitrogen-containing compounds, phosphorus-containing compounds, boron-containing compounds, or sulfur-containing compounds; more preferably, the material of the coating layer is a carbonaceous material.

[0086] In a fourth typical embodiment of the present invention, a negative electrode is also provided, the negative electrode comprising a negative electrode active material, the negative electrode active material comprising the silicon-carbon composite material provided in the third typical embodiment of the present invention.

[0087] In a fifth typical embodiment of the present invention, a battery is also provided, the battery comprising a positive electrode, a negative electrode, a separator or an electrolyte, wherein the negative electrode comprises a silicon-carbon composite material provided in a third typical embodiment of the present invention.

[0088] The technical solution of the present invention will be clearly and completely described below with reference to the embodiments. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0089] 1. Carbon materials

[0090] Example 1

[0091] A method for preparing a carbon material, specifically comprising the following steps:

[0092] Step 1: Preparation of a hard template-carbon composite using mesoporous carbon (S1): Weigh 5g of phenolic resin and dissolve it in 100mL of ethanol. Stir thoroughly for 20 minutes until the solution becomes transparent. Stir evenly and add 2.5g of commercially available micronized silica powder (pore volume 0.77cm³). 3 / g), stir vigorously for 2 hours; after the sample becomes viscous, carbonize it at 550℃ for 2 hours at a heating rate of 5℃ / min.

[0093] Step S2, washing to obtain carbon material: The carbonized material is washed twice with HF acid (1 mL HF plus 50 mL pure water), followed by multiple washes with pure water until the filtrate is neutral. This yields the desired mesoporous carbon material with a 0.5 wt% silica film adhering to the pore walls. The mesoporous carbon material in Embodiment 1 is as follows... Figure 1 As shown, the adsorption-desorption isotherms are as follows: Figure 2 As shown, the electron microscope scanning image is as follows: Figure 4 As shown.

[0094] Example 2

[0095] This embodiment provides a carbon material, the preparation method of which differs from that of Embodiment 1 in that: the phenolic resin in step S1 is replaced with sucrose, the solvent ethanol is replaced with pure water, and other conditions remain unchanged.

[0096] Example 3

[0097] This embodiment provides a carbon material, the preparation method of which differs from that of Embodiment 1 in that: the phenolic resin in step S1 is replaced with asphalt, the solvent ethanol is replaced with toluene, and other conditions remain unchanged.

[0098] Example 4

[0099] This embodiment provides a carbon material, the preparation method of which differs from that of Example 1 in that commercially available micronized silica gel is replaced with commercially available aluminum gel, while other conditions remain unchanged.

[0100] Example 5

[0101] This embodiment provides a carbon material, the preparation method of which differs from that of Embodiment 1 in that: the commercially available micronized silica gel in step S1 is replaced with laboratory-made porous silica gel, while other conditions remain unchanged.

[0102] The method for preparing the self-made porous silica gel is as follows:

[0103] (1) Add 0.3 mL of hexadecyltrimethylammonium bromide (CTAB) aqueous solution (1.0 wt%) to 10 mL of ethanol / water (1:3) solution and stir until CTAB is completely dissolved. Then add 0.75 mL of ammonia water and stir until homogeneous to obtain solution A; add 1.65 mL of tetraethyl orthosilicate (TEOS) to 2.3 mL of anhydrous ethanol solution and stir until homogeneous to obtain solution B. Then add solution B to solution A, seal the container and stir at room temperature for 24 h.

[0104] (2) Filter by suction and wash until the filtrate is neutral (pH=7). Dry the filter cake at 60℃ for 3 hours and then sinter at 600℃ for 5 hours with a heating rate of 2℃ / min. Grind the resulting material to obtain porous silica gel.

[0105] Example 6

[0106] The difference from Example 1 is that the ratio of phenolic resin to commercially available micronized silica gel is adjusted to 1:1.

[0107] Example 7

[0108] The difference from Example 1 is that the ratio of phenolic resin to commercially available micronized silica gel is adjusted to 3:1.

[0109] Example 8

[0110] The difference from Example 1 is that the ratio of phenolic resin to commercially available micronized silica gel is adjusted to 5:1.

[0111] Example 9

[0112] The difference from Example 1 is that the HF acid used for washing is replaced with NaOH (0.5 mol / L). Under 90°C conditions, a 0.2% silicon oxide film is attached to the pore walls of the mesoporous carbon material.

[0113] Example 10

[0114] The difference from Example 1 is that the HF acid used for washing is replaced with NaOH (0.5 mol / L) at room temperature, and a 5% silicon oxide film is attached to the pore walls of the mesoporous carbon material.

[0115] The pore parameters of the carbon materials prepared in Examples 1-10 are shown in Table 1, and the electrochemical performance parameters of the silicon-carbon composite materials prepared in Examples 11-20 are shown in Table 2.

[0116] Comparative Example 1

[0117] A method for preparing a carbon material, specifically comprising the following steps:

[0118] Step S1, Preparation of hard template-carbon composite: Weigh 5g of polyacrylonitrile (PAN) and dissolve it in a mixed solvent of 60mL dimethylformamide (DMF) and 40mL deionized water. Heat to 80℃ and stir thoroughly for 20min until the solution is completely dissolved. Stir evenly, add 2.5g of commercially available micronized silica gel (pore volume 0.77cm3 / g), and continue stirring vigorously for 2h. After the sample reaches a viscous state, carbonize it at 550℃ for 2h at a heating rate of 5℃ / min.

[0119] Step S2, washing to obtain carbon material: The carbonized material was washed twice with HF acid (1 mL HF + 50 mL pure water), followed by multiple washes with pure water until the filtrate was neutral. No oxides were detected in the obtained carbon material, indicating that no oxides adhered to the inner walls of the pores.

[0120] Comparative Example 2

[0121] Phenolic resin was directly carbonized at 550℃ for 2 hours with a heating rate of 5℃ / min. The adsorption-desorption isotherms of the resulting mesoporous carbon are shown below. Figure 3 As shown.

[0122] 2. Silicon-carbon composite materials

[0123] Example 11

[0124] This embodiment provides a silicon-carbon composite material, the preparation method of which is as follows:

[0125] Step S1: Provide a mesoporous carbon material, which is the carbon material obtained in Example 1;

[0126] Step S2: The mesoporous carbon from step S1 is broken down and classified to obtain mesoporous carbon powder with a dV50 of 8 μm.

[0127] Step S3: The mesoporous carbon powder obtained in step S2 is placed in a tube furnace and heated from room temperature to 550°C at a rate of 2°C / min in a N2 atmosphere; then the atmosphere is changed to a 20% SiH4-0.03% O2-N2 mixture and held at 550°C for 10 hours in the 20% SiH4-0.03% O2-N2 mixture; then a 10% C2H2-N2 mixture is introduced and held at 600°C for 1 hour; finally, the mixture is allowed to cool naturally in a N2 atmosphere to obtain the silicon-carbon composite material.

[0128] Example 12

[0129] This embodiment provides a silicon-carbon composite material, the preparation method of which is as follows:

[0130] Step S1: Provide a mesoporous carbon material, which is the carbon material obtained in Example 2;

[0131] Steps S2 and S3 are the same as steps S2 and S3 in Example 11.

[0132] Example 13

[0133] This embodiment provides a silicon-carbon composite material, the preparation method of which is as follows:

[0134] Step S1: Provide a mesoporous carbon material, which is the carbon material obtained in Example 3;

[0135] Step S2: The mesoporous carbon from step S1 is broken down and classified to obtain mesoporous carbon powder with a dV50 of 8 μm.

[0136] Step S3: The mesoporous carbon powder obtained in step S2 is placed in a tube furnace and heated from room temperature to 550°C at a rate of 2°C / min in a N2 atmosphere; then the atmosphere is changed to a 20% SiH4-0.08% O2-N2 mixture and held at 550°C for 10 hours in the 20% SiH4-0.08% O2-N2 mixture; then a 10% C2H2-N2 mixture is introduced and held at 600°C for 1 hour; finally, the mixture is allowed to cool naturally in a N2 atmosphere to obtain the silicon-carbon composite material.

[0137] Example 14

[0138] This embodiment provides a silicon-carbon composite material, the preparation method of which is as follows:

[0139] Step S1: Provide a mesoporous carbon material, which is the carbon material obtained in Example 4;

[0140] Step S2: The mesoporous carbon from step S1 is broken down and classified to obtain mesoporous carbon powder with a dV50 of 8 μm.

[0141] Step S3: The mesoporous carbon powder obtained in step S2 is placed in a tube furnace and heated from room temperature to 550°C at a rate of 2°C / min in a N2 atmosphere; then the atmosphere is changed to a 20% SiH4-0.03% O2-N2 mixture and held at 550°C for 8 hours in the 20% SiH4-0.03% O2-N2 mixture; then a 10% C2H2-N2 mixture is introduced and held at 600°C for 1 hour; finally, the mixture is allowed to cool naturally in a N2 atmosphere to obtain the silicon-carbon composite material.

[0142] Example 15

[0143] This embodiment provides a silicon-carbon composite material, the preparation method of which is as follows:

[0144] Step S1: Provide a mesoporous carbon material, which is the carbon material obtained in Example 5;

[0145] Step S2: The mesoporous carbon from step S1 is broken down and classified to obtain mesoporous carbon powder with a dV50 of 8 μm.

[0146] Step S3: The mesoporous carbon powder obtained in step S2 is placed in a tube furnace and heated from room temperature to 550°C at a rate of 2°C / min in a N2 atmosphere; then the atmosphere is changed to a 20% SiH4-0.01% O2-N2 mixture and held at 550°C for 10 hours in the 20% SiH4-0.01% O2-N2 mixture; then a 10% C2H2-N2 mixture is introduced and held at 600°C for 30 minutes; finally, the mixture is allowed to cool naturally in a N2 atmosphere to obtain the silicon-carbon composite material.

[0147] Example 16

[0148] This embodiment provides a silicon-carbon composite material, the preparation method of which is as follows:

[0149] Step S1: Provide a mesoporous carbon material, which is the carbon material obtained in Example 6;

[0150] Step S2: The mesoporous carbon from step S1 is broken down and classified to obtain mesoporous carbon powder with a dV50 of 8 μm.

[0151] Step S3: The mesoporous carbon powder obtained in step S2 is placed in a tube furnace and heated from room temperature to 550°C at a rate of 2°C / min in a N2 atmosphere; then the temperature is changed to a 20% SiH4-0.05% O2-N2 mixed gas and maintained at 550°C for 30 hours in the 20% SiH4-0.05% O2-N2 mixed atmosphere; then a 10% C2H2-N2 mixed gas is introduced and maintained at 600°C for 2 hours; finally, the temperature is allowed to cool naturally in a N2 atmosphere to obtain the silicon-carbon composite material.

[0152] Example 17

[0153] This embodiment provides a silicon-carbon composite material, the preparation method of which is as follows:

[0154] Step S1: Provide a mesoporous carbon material, which is the carbon material obtained in Example 7;

[0155] Step S2: The mesoporous carbon from step S1 is broken down and classified to obtain mesoporous carbon powder with a dV50 of 8 μm.

[0156] Step S3: The mesoporous carbon powder obtained in step S2 is placed in a tube furnace and heated from room temperature to 550°C at a rate of 2°C / min in a N2 atmosphere; then the atmosphere is changed to a 20% SiH4-0.02% O2-N2 mixture and held at 550°C for 7 hours in the 20% SiH4-0.02% O2-N2 mixture; then a 10% C2H2-N2 mixture is introduced and held at 600°C for 30 minutes; finally, the mixture is allowed to cool naturally in a N2 atmosphere to obtain the silicon-carbon composite material.

[0157] Example 18

[0158] This embodiment provides a silicon-carbon composite material, the preparation method of which is as follows:

[0159] Step S1: Provide a mesoporous carbon material, which is the carbon material obtained in Example 8;

[0160] Step S2: The mesoporous carbon from step S1 is broken down and classified to obtain mesoporous carbon powder with a dV50 of 8 μm.

[0161] Step S3: The mesoporous carbon powder obtained in step S2 is placed in a tube furnace and heated from room temperature to 550°C at a rate of 2°C / min in a N2 atmosphere; then the atmosphere is changed to a 20% SiH4-0.01% O2-N2 mixture and held at 550°C for 5 hours in the 20% SiH4-0.01% O2-N2 mixture; then a 10% C2H2-N2 mixture is introduced and held at 600°C for 30 minutes; finally, the mixture is allowed to cool naturally in a N2 atmosphere to obtain the silicon-carbon composite material.

[0162] Example 19

[0163] This embodiment provides a silicon-carbon composite material, the preparation method of which is as follows:

[0164] Step S1: Provide a mesoporous carbon material, which is the carbon material obtained in Example 9;

[0165] Steps S2 and S3 are the same as steps S2 and S3 in Example 11.

[0166] Example 20

[0167] This embodiment provides a silicon-carbon composite material, the preparation method of which is as follows:

[0168] Step S1: Provide a mesoporous carbon material, which is the carbon material obtained in Example 10;

[0169] Steps S2 and S3 are the same as steps S2 and S3 in Example 11.

[0170] Comparative Example 3

[0171] This embodiment provides a silicon-carbon composite material, the preparation method of which is as follows:

[0172] Step S1: Provide a mesoporous carbon material, which is the carbon material obtained in Comparative Example 1;

[0173] Step S2: The mesoporous carbon from step S1 is broken down and classified to obtain mesoporous carbon powder with a dV50 of 8 μm.

[0174] Step S3: The mesoporous carbon powder obtained in step S2 is placed in a tube furnace and heated from room temperature to 550°C at a rate of 2°C / min in a N2 atmosphere; then the atmosphere is changed to a 20% SiH4-0.2% O2-N2 mixture and held at 550°C for 12 hours in the 20% SiH4-0.2% O2-N2 mixture; then a 10% C2H2-N2 mixture is introduced and held at 600°C for 2 hours; finally, the mixture is allowed to cool naturally in a N2 atmosphere to obtain the silicon-carbon composite material.

[0175] Comparative Example 4

[0176] This embodiment provides a silicon-carbon composite material, the preparation method of which is as follows:

[0177] Step S1: Provide a mesoporous carbon material, which is the carbon material obtained in Comparative Example 2;

[0178] Step S2: The mesoporous carbon from step S1 is broken down and classified to obtain d V50 Mesoporous carbon powder with a diameter of 8 μm;

[0179] Step S3: The mesoporous carbon powder obtained in step S2 is placed in a tube furnace and heated from room temperature to 550°C at a rate of 2°C / min in a N2 atmosphere; then the temperature is changed to a 20% SiH4-N2 mixed gas and maintained at 550°C for 3 hours in a 20% SiH4-N2 mixed atmosphere; then a 10% C2H2-N2 mixed gas is introduced and maintained at 600°C for 30 minutes; finally, the temperature is allowed to cool naturally in a N2 atmosphere to obtain the silicon-carbon composite material.

[0180] 3. Testing Method

[0181] (1) N2 adsorption testing is a material characterization method well-known to those skilled in the art, and its specific test conditions will not be elaborated here. The specific surface area A of the carbon material is calculated using multi-point BET, and the settlement result satisfies the condition that the intercept C value > 0 and the correlation coefficient R. 2≥0.9999. The pore volume V was obtained based on the maximum adsorption amount when p / p0>0.99 in the N2 adsorption test, and the average pore size D = 4V / A*1000 (nm). The pore distribution of carbon materials can be estimated through the average pore size; when the average pore size D<2nm, the proportion of micropores is usually greater than 80%. The DFT method was used to fit the N2 adsorption-desorption isotherm to analyze the pore distribution of different pore sizes in the carbon material and obtain the content information of each pore size.

[0182] (2) Mass content of oxides in carbon materials

[0183] ICP-OES was used to test the silicon or aluminum content or the content of other metals in the hard template, and the corresponding oxide content was calculated.

[0184] (3) Test of Si content in silicon-carbon composite materials:

[0185] 3.0 g of silicon-carbon composite material was dried in a 150℃ oven until constant weight, and the mass m1 was recorded. The dried composite material was then placed in a muffle furnace, heated to 1100℃ and held for 2 hours, cooled, and weighed, and the mass m2 was recorded. The Si content calculation formula is as follows:

[0186]

[0187] (4) The following is a brief explanation of battery testing.

[0188] Half-cell testing method: The electrochemical performance of the silicon-carbon composite materials obtained in Examples 11-20 and Comparative Examples 3 and 4 was tested, and the results are shown in Table 1. Using the silicon-carbon composite materials obtained in Examples 11-20 and Comparative Examples 3 and 4 as the negative electrode active material, negative electrode sheets were prepared respectively. CR2032 coin cells were prepared using conventional methods for the negative electrode sheets, and the electrical performance of the cells was tested. Charge-discharge tests were performed on the cells using the LAND battery testing system.

[0189] (1) Half-cell assembly: Assemble CR2032 button cells in a glove box, with lithium metal sheet as counter electrode, polypropylene microporous membrane as separator, and LiPF6 dissolved in a mixture of ethyl carbonate (EC) and diethyl carbonate (DEC) (volume ratio EC:DEC=1:1), wherein the concentration of LiPF6 is 1mol / L.

[0190] (2) Cyclic specific capacity and initial efficiency test: After the CR2032 button cell was left to stand for 6 hours, it was discharged to 0.005V at 0.05C and then discharged to 0.005V at 0.01C; after standing for 5 minutes, it was charged to 1.5V at a constant current of 0.05C; the initial delithiation specific capacity at 0.8V is the specific capacity (or mass specific capacity) of the electrode material at 0.8V, and the ratio of the initial delithiation specific capacity at 0.8V to the initial lithium insertion specific capacity at 1.5V is the initial coulombic efficiency at 0.8V of the battery.

[0191] High-density half-cell testing method: After the negative electrode sheet is prepared using conventional methods, it undergoes further rolling to prepare a high-density negative electrode sheet. The compaction density of conventional electrodes is 0.8 g / cm3, while the compaction density of high-density electrodes is approximately 1.0 g / cm3.

[0192] Full-cell testing method: Using the silicon-carbon composite materials obtained in Examples 11-20 and Comparative Examples 3 and 4 as the negative electrode active material, pouch cells containing the negative electrode active material were prepared using conventional methods, and their electrical performance was tested. The pouch cells were prepared in a dehumidified room at a dew point of -45°C. Charge-discharge cycle tests were performed on the cells using the LANBTS battery testing system. The results are shown in Table 1. The specific test methods are as follows:

[0193] (1) Preparation of positive electrode sheet: The positive electrode active material LiCoO2, conductive agent Super P, binder PVDF and solvent NMP are mixed evenly in a mass ratio of 92:3:5:150 and then evenly coated on the positive electrode current collector. Then, it is dried at 80℃ to obtain the positive electrode sheet.

[0194] (2) Preparation of negative electrode sheet: The negative electrode active material, conductive agent Super P, binder polyacrylic acid and solvent deionized water are mixed evenly in a mass ratio of 95:1:4:120. The mixture is then evenly coated on the negative electrode current collector and dried at 100℃ to obtain the negative electrode sheet.

[0195] (3) The positive and negative electrode sheets are stacked in a square and separated by a polypropylene separator to form a battery cell, which is then packaged into an aluminum-plastic bag. An electrolyte of appropriate capacity is injected into the aluminum-plastic bag, and the bag is vacuum sealed to obtain a soft-pack battery. The electrolyte is a mixture of LiPF6 EC and DEC, wherein the concentration of LiPF6 is 1 mol / L and the volume ratio of EC to DEC is 1:1.

[0196] (4) Formation and Capacity Testing: After liquid injection and sealing, the battery begins formation. It is placed in a 25°C constant temperature chamber for 12 hours, then charged at a constant current of 0.02C to 3.3V, placed for 30 minutes, charged at a constant current of 0.025C to 3.8V, placed for 10 minutes, and charged at a constant current of 0.33C to 4.2V. After formation, the battery is vacuum-sealed and then subjected to capacity testing. It is charged at a constant current of 0.33C to 4.45V, placed for 10 minutes, discharged at a constant current of 1C to 3V, placed for 10 minutes, and discharged at a constant current of 0.33C to 3V. The capacity testing is then completed. The ratio of the discharge capacity to the charge capacity during the formation and capacity testing of the pouch battery is the battery's initial efficiency.

[0197] (5) 25℃ Cyclic Test: Place the battery in a 25℃ constant temperature chamber, charge it with a constant current of 1C to 4.45V, and then charge it with a constant voltage of 4.45V to a current of 0.1C; after standing for 10 minutes, discharge it with a constant current of 1C to 3.0V, and stand for 10 minutes. Repeat the above charging and discharging steps until the discharge capacity is lower than 80% of the discharge capacity of the first cycle. The number of cycles obtained at this time is the cycle life of the soft pack battery; record the capacity retention rate after 100 cycles.

[0198] Table 1. Physicochemical properties of the carbon materials obtained in Examples 1-10 and Comparative Examples 1 and 2

[0199]

[0200] Table 2. Physicochemical properties and electrochemical performance of the silicon-carbon composite materials obtained in Examples 11-20 and Comparative Examples 3 and 4.

[0201]

[0202]

[0203] Table 1 shows that the carbon materials prepared in Examples 1-10 contain oxides, which are located on the inner walls of the pores of the porous carbon framework, with a mass content of 0.2%-5.0%. All the obtained carbon materials contain mesopores, primarily ranging from 2 to 10 nm in size. In Example 1, phenolic resin was used as the carbon precursor, with a phenolic resin / silicone (hard template) ratio of 2:1, and the resulting mesoporous carbon material had a pore volume of 0.77 cm³. 3 / g, with an average pore size of 3.35nm; under suitable washing conditions, its oxide content is 0.5%; from Figure 2 The pore distribution of the N2 adsorption isotherm can be calculated using a DFT model. It can be seen that the mesopores in this embodiment contain pores of 2–10 nm, and the volume of pores of 2–10 nm accounts for 81.0% of the total pore volume. The SEM results of the carbon material in Example 1 are as follows: Figure 4As shown, no obvious mesopores >10nm appeared in the carbon material. Since Example 3 used pitch as the carbon precursor, and pitch has a lower pore volume after carbonization compared to resin (Example 1) and sucrose (Example 2), the mesopore content reached 98.4%, with 2-10nm mesopores accounting for 85.7%. Example 4 used alumina instead of silicon dioxide as the hard template, and the resulting carbon material had a pore volume of only 0.59cm³. 3 / g, this is because alumina has a higher density than silicon dioxide, resulting in a smaller permeable volume and consequently a smaller pore volume. In Examples 6-8, the phenolic resin / silicone ratio increased from 1:1 to 5:1, and the pore volume increased from 1.27 cm³ / g. 3 / g decreased to 0.36cm 3 / g, the mesoporous content decreased from 100% to 61.0%, indicating that a reduction in the proportion of template material leads to a decrease in pore volume. Adding an appropriate amount of oxide can significantly optimize the pore structure of carbon materials and improve their structural strength. In Example 10, the NaOH washing conditions were weaker, resulting in a higher residual SiO content of 5%, a mesoporous content of 71.2%, and an average pore size reduced to 2.98 nm. Compared with Example 1, Comparative Example 1, by replacing other organic materials such as PAN as the carbon precursor and washing away the hard template in the same way, resulted in carbon materials with no oxide adhering to the pore walls. In contrast, the carbon materials obtained using the carbon precursors selected in Examples 1-10 had a layer of oxide film covering the pore walls. Due to the strong bond between -CH- and -HO bonds, this oxide film was less likely to fall off and had stronger adhesion. Comparative Example 2 did not use a hard template and directly carbonized the resin, resulting in a significant reduction in pore volume and pore size, with a mesoporous content of only 5.8%.

[0204] Examples 11-20 used the carbon materials from Examples 1-10 as matrices for silicon deposition to obtain silicon-carbon composite materials. Table 2 lists the physicochemical and electrochemical properties of these composite materials. The performance of the silicon-carbon composite materials is closely related to the pore structure and composition of the carbon materials. In Examples 11-20, due to the use of a hard template agent in the carbon substrate, the pore volume was relatively large, resulting in silicon-carbon composite materials with a high silicon content, thus exhibiting a high specific capacity. The size of silicon nanoparticles in the CVD silicon-carbon composite materials is determined by the pore size of the porous carbon framework and the deposition process, and the pore size of the porous carbon framework determines the upper limit of the silicon particle size. By controlling the pore size distribution of the porous carbon framework, such as using mesopores of 2–10 nm as the main pore size, and employing a suitable deposition process, the size of silicon nanoparticles is controlled within 2–5 nm, significantly reducing silicon particle expansion during lithium intercalation of the silicon-carbon composite material and improving its cycling stability. Because the carbon substrate contains mesopores and a certain amount of oxides within the pores, the resulting silicon-carbon composite material exhibits high structural strength. Therefore, under high pressure density conditions, its initial efficiency at 0.8 V is only about 0.5–1.5% lower than under conventional conditions, and it possesses high cycling stability, with capacity retention exceeding 98.5% at 25°C and after 100 cycles. Specifically, Example 11 uses the mesoporous carbon material provided in Example 1 of this invention as the matrix, achieving a capacity retention as high as 99.5% and an initial coulombic efficiency of 85.3% at 0.8 V under high pressure density. Example 16 uses a macroporous ordered porous carbon material as the carrier, achieving a silicon content of 62.6% in the composite material, with a specific capacity of 2071 mAh / g at 0.8 V and a capacity retention of 98.6% at 25°C and after 100 cycles.

[0205] Comparative Example 4 uses the carbon material from Comparative Example 2 as a matrix, with a pore volume of only 0.22 cm³. 3 The resulting silicon-carbon composite material had a low silicon content and a specific capacity of only 799 mAh / g. Comparative Examples 3 and 4, due to the absence of oxides within the carbon substrate pores, resulted in silicon-carbon composite materials with lower structural strength, a reduction of over 3% in first-pass yield under high-pressure conditions compared to conventional conditions, and significantly lower cycle stability than Examples 11-20.

[0206] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, and not to limit them; although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that modifications can still be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some or all of the technical features; and these modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.

Claims

1. A carbon material, characterized in that, The carbon material comprises a porous carbon framework and oxides, wherein the oxides are located on the inner walls of the pores of the porous carbon framework, and the oxides are coated on the pore walls of the carbon material in the form of oxide films; and / or, the oxides exist on the pore walls of the carbon material in the form of oxide islands.

2. The carbon material according to claim 1, characterized in that, The oxide has a mass content of 0.2% to 5.0%; the carbon material contains mesopores with a pore size of 2 to 10 nm.

3. The carbon material according to claim 1, characterized in that, The oxide in the carbon material is one or more of silicon oxide, aluminum oxide, titanium oxide, aluminum silicate oxide, or magnesium oxide.

4. The carbon material according to claim 1, characterized in that, The mass content of oxides in the carbon material is 0.2% to 1.0%; And / or, the specific surface area of ​​the carbon material is 200–2000 m². 2 / g; And / or, the pore volume of the carbon material is 0.2–1.5 cm³. 3 / g; And / or, the average pore size of the carbon material is 2 to 10 nm; And / or, the carbon material has a mesoporous content of 75% to 100%; And / or, the pore volume of the 2-10 nm mesopores in the carbon material accounts for 75%-100% of the pore volume; And / or, the pore size of the intermediate pores in the carbon material is 2-5 nm; And / or, the carbon material is an ordered mesoporous material.

5. A method for preparing a carbon material, characterized in that, The carbon material is prepared by mixing a hard template agent with a carbon precursor, carbonizing the mixture, and then removing the hard template agent to obtain the carbon material. The carbon material is a mesoporous carbon material. The carbon precursor is an organic compound containing a carbon source, and the carbon source is one or more of polysaccharides, resins, or asphalt.

6. The preparation method according to claim 5, characterized in that, The hard template agent includes one or more of silicon oxide, aluminum oxide, titanium oxide, silicon aluminum oxide, or magnesium oxide; the hard template agent is a porous material. And / or, the mass ratio of the carbon precursor to the hard template agent is 1:50 to 10:1; And / or, the mixing includes solid-phase mixing or liquid-phase mixing, wherein the solid-phase mixing is to grind or ball-mill the carbon precursor and the hard template agent; and the liquid-phase mixing is to disperse the carbon precursor and the hard template agent in a solvent, wherein the solvent is pure water and / or ethanol, and the solvent is removed by solvent evaporation and / or solid-liquid separation. And / or, the carbonization temperature is 500–1000°C; And / or, the method of removing the hard template agent is to treat it with one or more of HF, NaOH, KOH, Na2CO3, K2CO3, HCl, HNO3 or H2SO4 at 0 to 110°C, and then clean and dry it; And / or, the method for preparing the carbon material further includes one or more of water activation, alkali activation, or defunctionalization treatment.

7. The preparation method according to claim 5, characterized in that, The preparation method of the hard template agent is as follows: the pH of a mixed slurry containing a surfactant, a catalyst and a hard template precursor is adjusted, and after hydrothermal treatment, the slurry is filtered, dried and calcined to obtain the hard template agent. The mass ratio of the surfactant to the hard template precursor is 1:100 to 100:1; The mass ratio of the surfactant to the catalyst is 1:30 to 30:1; The method for preparing the mixed slurry containing surfactant, catalyst and hard template precursor is to mix solution A containing surfactant and catalyst with solution B containing hard template precursor and adjust the pH. The surfactant is one or more of cationic surfactants, anionic surfactants, amphoteric surfactants, and nonionic surfactants; The catalyst includes an acid solution or an alkaline solution; The hard template precursor includes one or more of the following: ethyl polysilicate, silane, silica sol, silicon tetrachloride, sodium silicate, potassium silicate, aluminum nitrate nonahydrate, aluminum isopropoxide, or aluminum sec-butoxide. The pH of the mixed slurry is one of acidic, neutral or alkaline, wherein the acidic pH is 1 to 5, the neutral pH is 6.5 to 7.5, and the alkaline pH is 9 to 13. The mixed slurry is subjected to hydrothermal treatment under the specified pH conditions, and the hydrothermal temperature is 0–220°C. The calcination temperature is 200–800℃.

8. A silicon-carbon composite material, characterized in that, The silicon-carbon composite material comprises carbon material and silicon nanoparticles, wherein the size of the silicon nanoparticles is 2-5 nm; an oxide interface exists between the carbon material and the silicon nanoparticles, wherein the mass content of the oxide is 0.04%-4.0%.

9. The silicon-carbon composite material according to claim 8, characterized in that, The carbon material is the carbon material described in claims 1 to 4 or the carbon material prepared by the preparation method described in any one of claims 5 to 7.

10. The silicon-carbon composite material according to claim 8, characterized in that, The silicon-carbon composite material is obtained by chemical vapor deposition of a silicon-containing precursor on the carbon material at 150–1000°C. The silicon-containing precursor is selected from one or more of silane, silane, propane, halosilane, polysilane, thiophene and its derivatives or silanium and its derivatives; The chemical vapor deposition process introduces a precursor containing heteroatoms; the precursor containing heteroatoms includes at least one of oxygen-containing precursors, carbon-containing precursors, nitrogen-containing precursors, phosphorus-containing precursors, sulfur-containing precursors, or boron-containing precursors; the silicon-containing precursor and the precursor containing heteroatoms are contacted with the porous substrate in the following ways: the silicon-containing precursor and the precursor containing heteroatoms are contacted with the porous substrate alternately; or, the silicon-containing precursor and the precursor containing heteroatoms are contacted with the porous substrate simultaneously; or, the silicon-containing precursor and a mixed gas containing the silicon-containing precursor and the precursor containing heteroatoms are contacted with the porous substrate alternately, the silicon-containing precursor is continuously in contact with the porous substrate, and the precursor containing heteroatoms is intermittently introduced during this process.

11. The silicon-carbon composite material according to claim 8, characterized in that, The silicon-carbon composite material includes a coating layer located on the surface of the silicon-carbon composite material; the material of the coating layer is selected from at least one of solid electrolytes, conductive polymers, carbonaceous materials, metals, alloys, metal oxides, metal hydroxides, halogen-containing compounds, nitrogen-containing compounds, phosphorus-containing compounds, boron-containing compounds, and sulfur-containing compounds.

12. The negative electrode, characterized in that, The negative electrode comprises a negative electrode active material, which comprises a silicon-carbon composite material as described in any one of claims 8 to 11.

13. A battery, characterized in that, The battery comprises a positive electrode, a negative electrode, a separator or an electrolyte, wherein the negative electrode comprises a silicon-carbon composite material as described in any one of claims 8 to 11.